Sistem Pendukung Keputusan Pemilihan perumahan Berbasis Android dengan Metode Simple Additive Weigthing - Aso Sudiarjo; Ruuhwan Ruuhwan (Jurnal ICT : Information Communication & Technology, 2019)
Types of housing that are increasingly varied from the type of simple houses to luxury homes, where the house is a family need to be occupied in a relatively long time. Problems that occur consumers are sometimes difficult to choose the type of housing and location of houses to be purchased with long-term needs or for investment needs. This study aims to facilitate consumers in making decisions when determining the right type of housing and in accordance with the desired conditions. Therefore, as advances in information technology and the development of the Android operating system, system support in the selection of Android-based housing needs to be built, and the application of the Simple method Additive weighting for housing alternative selection. The SAW method concept is often referred to as the weighted sum method. There are six criteria to be taken into consideration, namely: distance to shopping centers, distance to education location, distance to health location, water availability, price and land area .. The method used in designing this application uses the Extreme Programming (XP) model. In the Extreme Programming (XP) method, there are 4 (four) stages in the Extreme Programming process: planning, design, coding, test. This system can support consumer decision making in choosing housing based on predetermined criteria. So that calculations on this decision support system are more accurate then an SAW method is used to determine the type of housing that matches the criteria sought by consumers.